VD_FINDINFO HC / 2014 / 8 vom 29. Januar 2014 - VD Tribunal cantonal (2014)
CONTRAT DE TRAVAIL, JUSTE MOTIF, RÉSILIATION IMMÉDIATE, RÉPRIMANDE, CERTIFICAT DE TRAVAIL | 330 al. 1 CO, 337 CO, 337c al. 1 CO, 337c al. 3 CO